Experimental study on accumulation of helium released into a semi-confined enclosure with distributed leaks. (31st March 2021) - Liang, Z.; McKenna, A.; Clouthier, T.; David, R.
Abstract: This paper examines the helium dispersion behavior in a 16.6 m 3 enclosure with a small opening in the floor and distributed leaks along the edges. Helium, a simulant for hydrogen, was injected near the center of the floor with an injection rate ranging from 2 to 50 standard liters per minute (Richardson number of 0.3–134) through an upward-facing nozzle. In a short-term transient, the helium distribution predicted with the models of Baines & Turner (1969) and Worster & Huppert (1983) matched the measured distributions reasonably well. In a long-term transient, the vertical helium profile always reached a steady state, which consisted of a homogenous layer at the top overlaying a stratified layer at the bottom. The helium transients in the uniform layer predicted with the models of Lowesmith (2009) and Prasad & Yang (2010), assuming a vent was located in the ceiling, were in good agreement with the measured transients. Highlights: Helium dispersion in an empty semi-confined enclosure. Helium distribution profile with low natural ventilation. Effect of distributed leaks on helium distribution. Predictive methods for helium distribution.